(648) New Elements in Financing Investments in Socialist Countries عناصر جديدة في تمويل الاستثمارات في الدول الاشتراكية - Fedorowicz, Zdzislaw (INP, 2024)
This paper discusses the evolution of the planning and management system in all socialist countries in Europe over a ten-year period. It was observed that this evolution is moving towards the substitution of directives issued by the central planning authority with a system of parameters that shape the independent decisions taken by socialist enterprises. However, this change in the planning and management system does not affect the role of central planning in the economic development of these countries. Regardless of the management system, the central economic plan always includes the most important objectives of economic development, such as the investment rate, the growth rate of national income, the growth rate of consumption, and the relationships between industrial sectors. This general economic development program is based on a particular pattern of final production, including a pattern of individual consumption, expressed in physical units, with monetary indicators used as tools for aggregating physical units. This detailed central economic plan is a necessary basis for all investment decisions, ensuring the balanced economic development of the national economy as a whole.